Sensing properties and photochromism of Ag–TiO2 nano-heterostructures. Issue 24 (6th June 2016) - Tobaldi, D. M.; Leonardi, S. G.; Pullar, R. C.; Seabra, M. P.; Neri, G.; Labrincha, J. A.
Abstract : Achieving advanced multifunctional materials displaying several coexisting properties is currently one of the most exciting and innovative research topics. Abstract : Achieving advanced multifunctional materials displaying several coexisting properties is currently one of the most exciting and innovative research topics. In this study, we report the engineering of a multifunctional material exhibiting, at the same time, tuneable photochromic behaviour and gas-sensing properties for acetone detection. The photochromic property of silver modified (1–10 mol% Ag) titanium dioxide (titania, TiO2 ) NPs was monitored under consecutive UVA-light exposure times, and the change in colour was thoroughly investigated with both spectroscopic and colourimetric analyses. All Ag modified samples exhibited a significant change in colour and visible spectra after only 15 seconds of exposure, and this increased with further exposure. It was shown that both the silver molar content in the Ag–TiO2 nano-heterostructure, as well as the UVA-light irradiation time, governed the tunability of the photochromic behaviour (the colour changed from pale yellow to dark blue in Ag-modified specimens, while it remained white in unmodified TiO2 ). The same nano-heterostructures were also tested as sensing materials for resistive metal oxide gas sensors (MOS). These Ag–TiO2 nano-heterostructures proved to be highly sensitive for the detection of acetone vapours at low concentrations (<1 ppm), superior to the best TiO2 -based sensors so far reported. This is the first thorough study to qualitatively monitor, in real-time, the growth of Ag 0 NPs on a TiO2 matrix, assessing both optical spectroscopy and colourimetric CIE L * a * b * analysis ( e.g. what meets the eye), and to also demonstrate the superior acetone gas-sensing properties of such nano-heterostructures.